2010
DOI: 10.1111/j.1468-3083.2010.03863.x
|View full text |Cite
|
Sign up to set email alerts
|

One‐stage reconstruction of deep facial defects with a single layer dermal regeneration template

Abstract: One-stage reconstruction with a combination of IDRT-SL and split thickness skin grafting is an elegant, easy and rapid method to treat deep skin defects. The take rates, functional and early cosmetic outcome are promising. This new method should be considered for selected cases of elderly multimorbid patients with deep facial wounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 14 publications
1
40
0
8
Order By: Relevance
“…There is a fair amount of literature on the use of Integra® for achieving acute wound closure secondary to trauma, oncological defects and necrotising infections [9][10][11][12]. The results are encouraging as Integra® is able to provide immediate wound coverage with few graft associated infections or graft failures.…”
Section: Introductionmentioning
confidence: 93%
“…There is a fair amount of literature on the use of Integra® for achieving acute wound closure secondary to trauma, oncological defects and necrotising infections [9][10][11][12]. The results are encouraging as Integra® is able to provide immediate wound coverage with few graft associated infections or graft failures.…”
Section: Introductionmentioning
confidence: 93%
“…Some dermal substitutes (e.g., , 1-mm -thick Matriderm ® , a bovine-based collagen I, III, and V and elastin hydrolysate dermal substitute) have also resulted in good clinical outcomes with a one-stage procedure (Haslik et al, 2007;Ryssel et al, 2008;Ryssel et al, 2010). Recently, a single-layer product, Integra ® (IDRT-SL ® ), was introduced for one-stage closure of deep facial surgical wounds in elderly multimorbid patients; studies have shown promising graft-take rates and good functional and cosmetic outcomes (Koenen et al, 2011). In this kind of Integra ® (IDRT-SL ® ) dermal substitute, the thickness is decreased to ~0.8-1 mm.…”
Section: Introductionmentioning
confidence: 97%
“…Several techniques have been established to reconstruct partial-thickness defects of the nasal ala. For smaller defects, these include second intention healing, side-to-side closure, delayed closure with serial tightening, full-thickness skin grafts, the myocutaneous island pedicle fl ap, the rhombic transposition fl ap, the Z-advancement fl ap, the keystone perforator island fl ap, or the bilobed fl ap. Larger defects may be closed using the cranially inserted nasolabial transposition fl ap (melolabial fl ap), the subcutaneous island pedicle fl ap, the shark island fl ap, the nasal dorsum transposition fl ap, the two-stage nasolabial interpolation fl ap or dermal regeneration templates as one-stage or two-stage procedures [ 1,[3][4][5][6][7][8][9][10][11][12] . Unfortunately, complication rates associated with an undesirable cosmetic outcome are highest for defects of the nasal ala and tip [ 13 ] .…”
Section: Introductionmentioning
confidence: 99%